2021
DOI: 10.1101/2021.12.28.474325
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deciphering the quality of SARS-CoV-2 specific T-cell response associated with disease severity, immune memory and heterologous response

Abstract: SARS-CoV-2 specific T-cell response has been associated with disease severity, immune memory and heterologous response to endemic coronaviruses. However, an integrative approach combining a comprehensive analysis of the quality of SARS-CoV-2 specific T-cell response with antibody levels in these three scenarios is needed. In the present study we found that, in acute infection, while mild disease was associated with high T-cell polyfunctionality biased to IL-2 production and inversely correlated with anti-S IgG… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…Our results also showed that Clec9A-RBD single dose immunization induced a potent and sustained antigen-specific poly-functional TH1 cellular response, consistent with our previous studies that targeted antigens to Clec9A-expressing cDC1 [16,42]. Poly-functional T cells have been proposed to represent a correlate of protection in other infectious diseases such as dengue and this feature is applicable towards COVID-19 as well [43][44][45]. Furthermore, Clec9A-RBD was able to elicit robust RBD-specific T cell memory that could be recalled 6-12 months postimmunization.…”
Section: Discussionsupporting
confidence: 90%
“…Our results also showed that Clec9A-RBD single dose immunization induced a potent and sustained antigen-specific poly-functional TH1 cellular response, consistent with our previous studies that targeted antigens to Clec9A-expressing cDC1 [16,42]. Poly-functional T cells have been proposed to represent a correlate of protection in other infectious diseases such as dengue and this feature is applicable towards COVID-19 as well [43][44][45]. Furthermore, Clec9A-RBD was able to elicit robust RBD-specific T cell memory that could be recalled 6-12 months postimmunization.…”
Section: Discussionsupporting
confidence: 90%
“…The SARS-CoV-2 specific CD4+ and CD8+ T cells were more related to protective immunity and immune memory against re-infection [16]. A recent study found that convalescent patients presented robust SARS-CoV-2 specific T cell response after seven-month infection [45]. Longer follow-up studies are needed to further understand mechanisms of protective adaptive immune responses to COVID-19.…”
Section: Discussionmentioning
confidence: 98%
“…1.5 × 10 6 PBMCs incubated with the proportional amount of DMSO were included in each experiment as a negative control. The stimulation was performed in the presence of 10 µg/mL of brefeldin A (Sigma Chemical Co) and 0.7 µg/mL of monensin (Golgi Stop, BD Biosciences) protein transport inhibitors, anti-CD107a-BV650 (clone H4A3; BD Biosciences) monoclonal antibody and purified CD28 (clone CD28.2) and CD49d (clone 9F10) (BD Biosciences) as previously described (67,68). Intracellular cytokines and cytotoxicity markers were analyzed by multiparametric flow cytometry.…”
Section: Sars-cov-2 Specific T Cell Responsementioning
confidence: 99%